The effects of beating, web forming and sizing on the surface energy of Eucalyptus globulus kraft fibres evaluated by inverse gas chromatography - Carvalho, Márcia (2005)
In this work attention has been focused on the effects of papermaking beating, web forming and sizing operations on the physical/chemical surface properties of bleached Eucalyptus globulus kraft fibres. Inverse gas chromatography (IGC) was used to determine the dispersive component of surface tension (cs d) as well as the acidic/basic character (according to the Lewis concept) of the solid surfaces (pulp fibres and pulp handsheets). The results have shown that the main effect of beating is to increase the fibre’s Lewis acidic character. Web forming caused a strong decrease in cs d and significant increments in the adhesion works of both acidic and basic probes, lowering the ratio between the two. Nevertheless, the surface of handsheets still exhibited a dominant acidic character. The sizing operation did not change the dispersive component of the surface tension significantly but decreased the difference between the adhesion works of the acidic and basic probes, rendering the handsheet surface less Lewis acidic and more Lewis basic. Thus, although internal sizing is expected to strongly influence liquid spreading at the paper surface and liquid penetration of the fibre’s network, it is concluded that beating and web forming lead to important changes in the surface energetic properties of the Eucalyptus globulus kraft fibres.